2019
DOI: 10.9734/jerr/2018/v3i416884
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Current Status of Municipal Solid Waste Management in Nigeria: Problems and Solutions

Abstract: The management of MSW is a major concern in several cities of developing countries due to its public health and environmental sustainability implications. This paper thus presents an overview of the current solid waste management practices and problems in some selected states in Nigeria. In addition to the comprehensive review of MSW generation, its characterization, collection, and treatment options in the considered states, an attempt was made to evaluate the major waste–to–energy indicators such as calorifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 22 publications
(22 reference statements)
0
13
0
Order By: Relevance
“…In Nigeria, Sridhar et al (2017) (Salami et al, 2018). In Benin City and environs, the MEPU is the regulatory ministry obligated to manage the environment on behalf of the Edo State Government.…”
Section: Overview Of Solid Waste Management In Nigeriamentioning
confidence: 99%
See 2 more Smart Citations
“…In Nigeria, Sridhar et al (2017) (Salami et al, 2018). In Benin City and environs, the MEPU is the regulatory ministry obligated to manage the environment on behalf of the Edo State Government.…”
Section: Overview Of Solid Waste Management In Nigeriamentioning
confidence: 99%
“…It is because the government agencies feel that urban SWM is the sole responsibility of the government. Salami et al (2018) found that the amount of waste generated across Nigeria's cities has increased, but the management strategies are inadequate. For example, many of the states agreed to create dumpsites as the best available option.…”
Section: Overview Of Solid Waste Management In Nigeriamentioning
confidence: 99%
See 1 more Smart Citation
“…The production of dangerous chemical wastes by cities, such as hospitals and factories, which now causes breathing issues and early deaths, is another recent development in MSWM [3]. Nigeria has recently emerged as a market for recycling, despite the fact that recycling has not met the required standards [4]. Poor MSW management at landfill sites frequently draws animals, rodents, mosquitoes, vultures, and scavengers, which could have a negative impact on front-line workers' health or even result in their demise [1].…”
Section: Introductionmentioning
confidence: 99%
“…These wastes include: cartons, papers, animals bones, plastics, aluminium plates, nylon bags, ceramics, vegetable stems, electronics, computers, photocopiers, aluminium cans, etc. Nigeria is the biggest contributors to solid waste in Africa with an estimated 32 million tons per year [8] [9] [10] [11] [12]. Coconut shell wastes are produced in large quantity in most tropical countries worldwide as Coconut forms a regular part of the human diets and other uses: food, drinks, oil, decorations, charcoal, cosmetics, etc.…”
Section: Introductionmentioning
confidence: 99%